Un monde relationnel d'opposition ou de don mutuel? - Mattheeuws, Alain (Marriage, families & spirituality, 2025)
Two authors are cited and studied to highlight the goodness and beauty of human relationships, particularly between men and women. Rereading the master-slave dialectic through that of men and women already shows how the conflictual and negative structure of the relationship has been overcome. G. Fessard opens up a path for us to attest to the prior quality of goodness in all male-female relationships. Another French philosopher, C. Bruaire, leads us down a similar path with his metaphysical reflection, which defines human beings as 'beings of gift' and 'beings of spirit'. The consequences of this reflection attest to the profound communion that is possible in male-female relationships thanks to the freedoms given to them. By giving themselves to others, all human beings fulfil themselves and develop their full potential. The relationship between men and women acquires the status of a mutual, reciprocal, and open gift: love is possible and will be fruitful. A distinction between two anthropologies is made in conclusion, shedding light on the present and future of all human relationships.